الفكر الديني روافده ونقده في المجتمع الغربي (مجلة الواحات للبحوث والدراسات, 2023)
ملخص:لدى معظم الأمم، يشكل الدين الحصن المنيع لمجموع المعارف والأفكار والمعتقدات التي تماهت مع قداسته، فكان نقد الدين عنصرا محوريا في الفكر الغربي، وتشكلت بذلك هوية ومنظومة دوغمائية أصابت العقل الغربي بشلل معرفي لزم هذا العقل طيلة فترة القرون الوسطى. إن مجرد تعريض الدين لآلية النقد، يعني وضع هذه المنظومة بأكملها أمام المساءلة والتشكيك، والمطالبة بتحرير العقل من سجن هوية أصبحت تشكل عبئا على تطور أوروبا التواقة لعصور واعدة، فنقد المنظومة الدينية تشير إلى تحولات أساسية في فكر التنوير وأعلامه. كلمات دالة: الفكر، الدين ، النقد، الهوية ، الخطاب ،                                      Abstract:Religion was the bulwark of all knowledge, ideas, and beliefs that identified with his holiness, so criticism of religion is a pivotal factor in Western thought, so an identity and a dogmatic system that struck the Western mind formed a cognitive paralysis that bound this mind throughout the medieval period. The mere exposure of religion to the criticism mechanism means putting this entire system in front of accountability and skepticism, and demanding the emancipation of the mind from the imprisonment of an identity that has become a burden on the development of Europe eager for promising ages. Criticism of the religious system indicates fundamental shifts in Enlightenment thought and its flags.Key words: Thought , Religion , Criticism , Identity , Discourse